PENGARUH KOMPETENSI DAN PENGAWASAN TERHADAP PRODUKTIVITAS KARYAWAN - Bahri, Zulmauli; Yulianita, Neni (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study examines the effect of competence and supervision on employee productivity at PT. A B C. The data used in this study is primary data, namely responses to questionnaires from 30 respondents. The method used is a quantitative method using multiple linear regression analysis. Simultaneous test results state that competence and supervision together have a significant effect on employee productivity. This is because the company provides work in accordance with the skills possessed by employees and in their work, superiors supervise so as to reduce errors that occur. The results of partial competency testing have a positive and significant effect on employee productivity. This means that the work given to employees is in accordance with the competencies possessed by employees who can support company goals. The results of the partial test of supervision have a positive and significant effect on employee productivity. This variable has a very significant effect on productivity, which proves that the company carries out good supervision, without supervision from the manager/superior, the plans that have been set will be difficult to implement properly by subordinates and this variable is a finding in research. The results of the determination test obtained an adjusted R square value of 0.308 meaning that competence and supervision have an influence contribution of 30.8% on employee productivity, while the remaining 69.2% of the productivity variable is contributed by other variables not examined. Keywords: Competence, Supervision, Employee Productivity